The cooperative as a case for democratization and development Focusing on Giporlos Credit Cooperative. - Balais, Ryan E. (Tacloban City Ryan E. Balais, 2009)
Cooperatives nowadays are believed as a vehicle for empowerment, development and democratization (TAGEM 2006). It is identifies as a means not only in empowering but also developing the citizens' economic condition specially the marginalized sector. This study was guided by the Political Efficacy Thesis of S.M. Lipet, Phillips Cutright and Kenneth Bollen which explains that economic development brings about better political communication and education among citizens, resulting for their clamor for a substantial role in politics and public affairs. Moreover this inquiry, attempts to generally describe the mechanisms used by the Giporlos Credit Cooperative (GCC) in empowering and financially developing its members through their strategies for capital buildup, popular participation, marketing strategies and the member's feedback towards its performance. This study center center upon the role of the Giporlos Credit Cooperative (GCC) in the democratic and economic context of development.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science